Hubungan Antara Asupan Energi dengan Rasio Neutrofil Limfosit pada Pasien Sakit Kritis - Dian Purwantini; Yohannessa Wulandari; Diana Sunardi; Krisadelfa Sutanto; Wina Sinaga; Diyah Eka Andayani (Majalah Kedokteran Indonesia, 2025)
Introduction: Critically-ill patients experience catabolic stress and inflammatory responses resulting in increased catabolism to meet energy demands. Neutrophil lymphocyte ratio (NLR) is used to assess immune and stress responses. Method: This study was a cross-sectional study of subjects aged ≥18 years admitted to the intensive care unit of Dr. Cipto Mangunkusumo National Central General Hospital and University of Indonesia Hospital. The characteristics of the study subjects included age, gender, nutritional status, diagnosis of ICU admission, protein intake, fat intake, and carbohydrate intake. Bivariate analysis was performed to evaluate the correlation between energy intake and neutrophil-lymphocyte ratio.Result: There were 44 subjects with a median age of 55 years (19-86). Nutritional status based on body mass index (BMI) obtained 31.8% normal nutritional status, 20.5% severe malnutrition, 25% obesity grade 1. The most common diagnoses were surgery and trauma 20.5% of subjects and sepsis 20.5% of subjects. Median RNL was 10.39 (2.51-59.5), energy intake was 10.5 (3-29) kcal/kg BW/day, protein intake was 0.4 (0-1.2) g/kg BW/day, fat intake was 18 (0-29)% and carbohydrate intake was 92 (23-184) g/day.Conclusion: There was no correlation between energy intake and NLR.